TRANSFORMASI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS DIGITAL DALAM MENGHADAPI GENERASI ALPHA - Fadhlul Munif, Raihan; Kurniawan, Fadhil Abi; Azma, Lukluk; Ritomas; Mahfuza, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology has significantly changed the educational paradigm, including in Islamic Religious Education (PAI) learning. The presence of Generation Alpha, born and raised amidst digital technological advancements, demands a transformation of learning media that is more interactive, visual, adaptive, and technology-based. This study aims to analyze the transformation of digital-based Islamic Religious Education learning media in addressing the characteristics of Generation Alpha, identify opportunities and challenges for its implementation, and formulate strategies for developing effective and relevant learning media. The study used a descriptive qualitative approach with a library research method through a review of various scientific journals, academic articles, and literature related to the digital transformation of Islamic education. The results show that the transformation of digital-based PAI learning media is carried out through the use of Learning Management Systems (LMS), interactive videos, gamification, educational social media, Artificial Intelligence (AI), Virtual Reality (VR), and Islamic digital learning applications. Digital media can increase learning motivation, student engagement, and learning effectiveness in accordance with the characteristics of Generation Alpha, which is visual, fast, and interactive. However, digital transformation also faces challenges such as low teacher digital literacy, limited infrastructure, the threat of digital moral degradation, and the risk of technological dependency. Therefore, it is necessary to strengthen the digital competence of Islamic Education teachers, integrate Islamic values ​​into digital media, and develop humanistic and adaptive learning strategies so that the transformation of learning media can support quality Islamic education in the digital era.